SIP1 and SIX1 are inversely correlated in hepatocellular carcinoma - Ercin, P.; Yalim-Camci, I.; Cetin, M.; Odabas, G.; Yagci, T. (Wiley-Blackwell, 2016)
[No abstract available]
41st FEBS Congress on Molecular and Systems Biology for a Better Life -- SEP 03-08, 2016 -- Kusadasi, TURKEY